Personality Profile of the Iranian Accountants - Ahmad Moddares; Halimeh Rahmani (پژوهش‌های تجربی حسابداری, 2011)
The purpose of this study is examining and determining the personality profile of the accounting students and professional accountants. The Five-Factor Model of Personality (NEO) is used for that purpose. The sample was consisted of 97 accounting students and 80 professional accountants. A descriptive and inferential analysis is used for analyzing the data. In order to test the hypothesis, Independent Samples t-Test and one sample T Test is used. The results suggest that about 70.52% of accounting students, 55.69% of professional accountants, and 63.79% of overall accountants have conscientiousness personality profile (C). Also, there are not any significant differences between the personality profile of the accounting students and professional accountants. Furthermore, at the level of 5% significant, the accountants' personality profile is conscientiousness personality profile (C). These results can be used in accounting education context.